2011
DOI: 10.1007/s10750-011-0812-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiological consequences of the supralittoral fringe: microhabitat temperature profiles and stress protein levels in the tropical periwinkle Cenchritis muricatus (Linneaus, 1758)

Abstract: Habitat selection by marine snails is profoundly affected by variations in biotic and abiotic factors. In the supralittoral fringe of Caribbean rocky shores, the littorinid Cenchritis muricatus endures a near-terrestrial existence through a combination of active microhabitat choice and, during dry periods, repose. In this study, we sought to compare knobby periwinkle body size, thermal load, water loss, and stress protein expression among common supralittoral microhabitats to determine the physiological conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 62 publications
(108 reference statements)
6
22
0
Order By: Relevance
“…Since both species occupy the same thermal niche, and were acclimated to the same temperature, the authors concluded that although congeneric, these species may have different evolutionary histories influencing their sub-cellular response to thermal stress. Judge et al (2011) had previously reported subcellular responses to thermal stress in tropical gastropods, which were not fully concordant with the microhabitat and temperature that they endured, concluding that detailed information on the specimens' physiological state and prior conditions was needed.…”
Section: Discussionmentioning
confidence: 95%
“…Since both species occupy the same thermal niche, and were acclimated to the same temperature, the authors concluded that although congeneric, these species may have different evolutionary histories influencing their sub-cellular response to thermal stress. Judge et al (2011) had previously reported subcellular responses to thermal stress in tropical gastropods, which were not fully concordant with the microhabitat and temperature that they endured, concluding that detailed information on the specimens' physiological state and prior conditions was needed.…”
Section: Discussionmentioning
confidence: 95%
“…With predictions of hotter air temperatures and an increased frequency of extreme-heat events associated with global climate change ( IPCC, 2013 ), the survival and persistence of some intertidal species is likely to be challenged further. To predict the future fate of species and populations, ecologists have collected baseline rock temperature data ( Helmuth, 1999 ; Denny et al, 2011 ; Judge, Botton & Hamilton, 2011 ; Gunderson et al, 2019 ), created heat budget models ( Helmuth, 1999 ; Choi et al, 2019 ), investigated how x species is affected by y substrate temperature ( Raimondi, 1988 ; Lathlean, Ayre & Minchinton, 2012 ; Lathlean, Ayre & Minchinton, 2013 ; Lamb, Leslie & Shinen, 2014 ), or used biomimetic loggers to investigate how internal body temperatures can be variously affected by environmental temperature ( Helmuth & Hofmann, 2001 ; Seabra et al, 2011 ; Lathlean et al, 2015 ; Seuront et al, 2019 ). All of these studies confirm that temperature is an important driving force that can influence the distribution of species on rocky seashores.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing across studies that investigate substratum temperature, a number of rock temperature observations have been made. Rock temperature is affected by its colour ( Raimondi, 1988 ; Judge, Botton & Hamilton, 2011 ; Gunderson et al, 2019 ), size and orientation relative to the sun ( Bertness, 1999 ; Chapperon et al, 2016 ; Chapperon, Studerus & Clavier, 2017 ). Marshall, McQuaid & Williams (2010) reported lighter-coloured sandstone was cooler than darker-coloured ferruginous sandstone.…”
Section: Introductionmentioning
confidence: 99%
“…Gastropods have been found to reduce body temperatures through avoidance behaviors such as orienting their shell to minimize surface area exposed to the sun in the summer (Muñ oz et al, 2005), by taking refuge on east facing rocks or in shaded crevices in the rocky intertidal (Williams and Morritt, 1995), or by hiding under tree roots in mangroves (Chapperon and Seuront, 2011). These and other studies have shown that there can be large differences in body temperatures depending on behavioral avoidance (Gömez-Cornejo, 1993;Williams and Morritt, 1995;Muñ oz et al, 2005Muñ oz et al, , 2008Williams et al, 2005;Chapperon and Seuront, 2011;Judge et al, 2011;Miller and Denny, 2011), though it is acknowledged that microhabitat selection can also be influenced by biotic factors (Williams and Morritt, 1995;Muñ oz et al, 2005Muñ oz et al, , 2008Chapperon and Seuront, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Barnes, 1958;Southward, 1958;Foster, 1971;Wolcott, 1973;Wethey, 1983). For instance, a number of studies have focused on correlations between body temperatures and microhabitat selection for intertidal gastropods (Wolcott, 1973;Gömez-Cornejo, 1993;Williams and Morritt, 1995;Muñ oz et al, 2005Muñ oz et al, , 2008Williams et al, 2005;Chapperon and Seuront, 2011;Judge et al, 2011). Gastropods have been found to reduce body temperatures through avoidance behaviors such as orienting their shell to minimize surface area exposed to the sun in the summer (Muñ oz et al, 2005), by taking refuge on east facing rocks or in shaded crevices in the rocky intertidal (Williams and Morritt, 1995), or by hiding under tree roots in mangroves (Chapperon and Seuront, 2011).…”
Section: Introductionmentioning
confidence: 99%